Modernisation of EU State aid procedures: are the rights of third parties more protected? - Anduena Gjevori (Juridical Tribune, 2015)
Despite the important role in increasing efficiency of the State aid control and in revealing the existence of State aid, third parties in EU State aid procedures are considered merely as a “source of information”. This article provides a critical analysis of the reforms of State aid procedures from a third party perspective. The reforms are disappointing maintaining the bilateral character of State aid procedures between two main parties the Commission and the Member States concerned and leaving third parties with very limited procedural rights. In addition the hard-law reform of the State aid procedures of 2013 increases the procedural duties of third parties without procedural guarantees and extends the investigatory powers of the Commission.